DEVELOPING A HUMAN CAPITAL MODEL FOR DIGITAL TRANSFORMATION IN THE SMART-FSM-BASED SECURITY OUTSOURCING INDUSTRY - Yakub Gunawan; Rhian Indradewa; Unggul Kustiawan; Ketut Sunaryanto (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
Digital transformation has significantly reshaped the security outsourcing industry, requiring organizations to develop human resources capable of operating within technology-driven environments supported by Smart Field Service Management (Smart-FSM). Despite substantial investments in digital technologies, many organizations continue to face challenges in developing a workforce that possesses both security-related competencies and digital capabilities necessary to support operational effectiveness and service quality. This study aims to develop a Human Capital model to support digital transformation in the Smart-FSM-based security outsourcing industry. The study adopts a qualitative approach using a conceptual research method based on literature analysis and the synthesis of theories related to Human Capital, Digital Transformation, Talent Management, and Knowledge Management. The research process involved identifying digital competency requirements, examining relevant Human Capital dimensions, and developing an integrated conceptual model aligned with Smart-FSM implementation. The findings resulted in the development of a Human Capital model consisting of seven key dimensions: Digital Workforce Planning, Digital Recruitment and Selection, Learning and Development, Performance Management, Talent Management, Knowledge Management, and Employee Retention. The proposed model contributes to the development of a digitally adaptive security workforce, enhances service quality, strengthens customer satisfaction, and supports long-term business sustainability. Therefore, the model may serve as a strategic reference for security outsourcing companies seeking to implement sustainable digital transformation initiatives. ABSTRAK Transformasi digital telah secara signifikan membentuk kembali industri outsourcing keamanan, yang mengharuskan organisasi untuk mengembangkan sumber daya manusia yang mampu beroperasi dalam lingkungan berbasis teknologi yang didukung oleh Smart Field Service Management (Smart-FSM). Terlepas dari investasi besar dalam teknologi digital, banyak organisasi terus menghadapi tantangan dalam mengembangkan tenaga kerja yang memiliki kompetensi terkait keamanan dan kemampuan digital yang diperlukan untuk mendukung efektivitas operasional dan kualitas layanan. Studi ini bertujuan untuk mengembangkan model Modal Manusia untuk mendukung transformasi digital dalam industri outsourcing keamanan berbasis Smart-FSM. Studi ini mengadopsi pendekatan kualitatif menggunakan metode penelitian konseptual berdasarkan analisis literatur dan sintesis teori yang berkaitan dengan Modal Manusia, Transformasi Digital, Manajemen Bakat, dan Manajemen Pengetahuan. Proses penelitian melibatkan identifikasi persyaratan kompetensi digital, pemeriksaan dimensi Modal Manusia yang relevan, dan pengembangan model konseptual terintegrasi yang selaras dengan implementasi Smart-FSM. Temuan menghasilkan pengembangan model Modal Manusia yang terdiri dari tujuh dimensi utama: Perencanaan Tenaga Kerja Digital, Rekrutmen dan Seleksi Digital, Pembelajaran dan Pengembangan, Manajemen Kinerja, Manajemen Bakat, Manajemen Pengetahuan, dan Retensi Karyawan. Model yang diusulkan berkontribusi pada pengembangan tenaga kerja keamanan yang adaptif secara digital, meningkatkan kualitas layanan, memperkuat kepuasan pelanggan, dan mendukung keberlanjutan bisnis jangka panjang. Oleh karena itu, model ini dapat berfungsi sebagai referensi strategis bagi perusahaan outsourcing keamanan yang berupaya menerapkan inisiatif transformasi digital yang berkelanjutan.